2005
DOI: 10.1093/humrep/deh701
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of microsurgical varicocelectomy on human sperm DNA integrity

Abstract: Our data suggest that varicocelectomy can improve human sperm DNA integrity in infertile men with varicocele. These data represent the first report of improved sperm DNA integrity after therapy and further support the beneficial effect of varicocelectomy on human spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
4

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(108 citation statements)
references
References 42 publications
7
96
1
4
Order By: Relevance
“…The prevalence of varicocele (63%) was increased in patients with high DFI compared to 35-40% incidence of varicoceles reported for infertile men in general [Zini 2007]. The reduction in levels of ROS and the improvement of sperm DNA integrity has been reported after surgical treatment of varicocele [Zini et al 2005]. We have also observed the positive effect of surgical correction of varicocele on sperm DNA damage.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The prevalence of varicocele (63%) was increased in patients with high DFI compared to 35-40% incidence of varicoceles reported for infertile men in general [Zini 2007]. The reduction in levels of ROS and the improvement of sperm DNA integrity has been reported after surgical treatment of varicocele [Zini et al 2005]. We have also observed the positive effect of surgical correction of varicocele on sperm DNA damage.…”
supporting
confidence: 70%
“…Several studies showed positive results in the treatment of patients with moderate DNA damage using oral antioxidants [Agarwal et al 2004;Greco et al 2005;Menezo et al 2007], microsurgical varicocelectomy in patients with varicocele [Zini et al 2005] and antibiotics in patients with Chlamydia and Mycoplasma infection [Gallegos et al 2008]. The data regarding treatment of patients with high DNA damage is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…• Unexplained or idiopathic infertility 26 • When deciding between IUI or IVF/ICSI as therapeutic options 37 • In the setting of varicocele-associated infertility 38 • Recurrent pregnancy loss 39 …”
Section: Sperm Chromatin Dispersionmentioning
confidence: 99%
“…Varicoceles have been shown to increase oxidative stress levels in the testes as well as in the semen. Varicocelectomy, in the other hand, may decrease seminal oxidative stress, increase seminal concentrations of antioxidants and also improve sperm quality [39]. In recent years, interest has increased regarding the role of antioxidants and B-vitamins as modulators of fertility [40][41][42][43].…”
Section: What Is New In Treament Antioxidant Therapymentioning
confidence: 99%
“…Several studies have demonstrated that the surgical treatment of clinical varicoceles is highly effective to decrease seminal oxidative stress, to increase seminal concentrations of antioxidants and to improve sperm quality [39,[45][46][47]. However, a meta-analysis of seven randomized, controlled trials of varicocele repair for male subfertility concluded that treatment of varicocele in men from couples with otherwise unexplained subfertility could not be recommended [48].…”
Section: Microsurgical Repair Of Clinical Varicocelementioning
confidence: 99%